THE HISTORY AND DYNAMICS OF FORMAL ISLAMIC EDUCATION INSTITUTIONS IN KAUR REGENCY, BENGKULU PROVINCE - Juliansyah, Juliansyah (Conciencia, 2023)
The purpose of the research is to analyse the history and dynamics of formal Islamic education institutions in Kaur Regency, Bengkulu Province. The type of research used is field research, with a descriptive qualitative approach. This method is to describe what it is about the History and Dynamics of the Development of Islamic Education Institutions in Kaur Regency, must be described as it is, with the aim of understanding the meaning contained in the history. In its implementation, the historical research method requires auxiliary sciences such as Sociology of educational sciences, Islamic Cultural History, and others. The results of the research show that, the history and dynamics of the development of Islamic institutions have now begun to appear with the support of the government and the changing understanding of the community about the importance of Islamic education. And so far, which is a factor in the difficulty of developing Islamic educational institutions, because it is affected by social changes in society, including community understanding, community economic factors, so that people to establish Islamic educational institutions are very constrained by funding, this is in line with the theory of dynamics.  Social dynamics occur as a result of interactions between people and between groups, so that between them there is a process of mutual influence that causes dynamics. Social dynamics occur in society in the form of changes in social values, norms prevailing in society, patterns of individual behaviour and organisations, the structure of social institutions, layers and classes in society, power and authority. In other words, social change includes changes in social organisation, status, institutions and the social structure of society. In addition, the slow development of Islamic education in Formal Schools is also a factor due to the lack of teachers who are civil servants, so automatically if most teachers are honorarium teachers, there is often a change of teachers, which is inseparable from the long historical dynamics influenced by the Dutch and Japanese colonisation.